SGS-LTER 1996 proposal - Shortgrass Steppe Long Term Ecological Research (SGS-LTER), author (Colorado State University. Libraries, 1996)
The shortgrass steppe (SGS) occupies the middle of the productivity gradient along which the LTER grassland sites lie. It is unique among North American grasslands for its long evolutionary history of intense selection by both drought and herbivory, leading to an ecosystem that is very well adapted to withstand grazing by domestic livestock. The distinctive features of the SGS are both its vegetation and the concentration of biological activity and organic matter belowground. The vegetation of the SGS is characterized by lowgrowing plants that are either tolerant or resistant to grazing and drought. The large concentration of biological activity belowground reflects the distribution of plant production (Milchunas and Lauenroth 1992) and the enhanced rates of energy flow through heterotrophs belowground (Lauenroth and Milchunas 1992). It is also explained in part by the fact that most biologically active elements in grasslands are protected from natural disturbances by being stored in soil organic matter (SOM). The SGS LTER project has been in operation since 1982, and currently supports 46 longterm experiments, numerous shortterm experiments, and has a large emphasis in integrative simulation analysis. SGS LTER work is divided into 5 major areas: populations and processes, biogeochemical dynamics, paleoecology and paleopedology, water and energy dynamics, and disturbances.
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: long term ecological research; shortgrass steppe; grassland ecology; Pawnee National Grassland; Central Plains Experimental Range